2014
DOI: 10.1111/neup.12171
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a panel of in‐house polyclonal antibodies for the diagnosis of enterovirus infections

Abstract: The aim of this study was to establish a reliable method of virus detection for the diagnosis of critical enterovirus infections such as acute infective encephalitis, encephalomyelitis and myocarditis. Because histopathological and immunohistochemical analyses of paraffin-embedded tissues play an important role in recognizing infectious agents in tissue samples, six in-house polyclonal antibodies raised against three representative enteroviruses using an indirect immunofluorescence assay and immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Highly neurotropic viruses such as poliovirus, enterovirus 71, and neurovirulent flaviviruses, infect the CNS and cause viral meningitis or encephalomyelitis, which is characterized by neuronal damage and perivascular inflammation [67][68][69][70]. The preferential target of these neurotropic viruses is the large pyramidal neurons in the human CNS (and in that of animal models) [38,71,72]. In this study, the two SAFV-3 strains only infected neural progenitor cells and glial cells around the lateral ventricles and cerebellum in both neonatal and young mice.…”
Section: Discussionmentioning
confidence: 99%
“…Highly neurotropic viruses such as poliovirus, enterovirus 71, and neurovirulent flaviviruses, infect the CNS and cause viral meningitis or encephalomyelitis, which is characterized by neuronal damage and perivascular inflammation [67][68][69][70]. The preferential target of these neurotropic viruses is the large pyramidal neurons in the human CNS (and in that of animal models) [38,71,72]. In this study, the two SAFV-3 strains only infected neural progenitor cells and glial cells around the lateral ventricles and cerebellum in both neonatal and young mice.…”
Section: Discussionmentioning
confidence: 99%
“…(34) The result of applying six different rabbit pAbs in WB and IHC, showed these antibodies can screen and determine various enterovirus antigens and be sensitive for some serotype classification. (35) In another study, the activity of purified pAbs was evaluated and confirmed through different laboratory methods. Their results revealed that the raised rabbit-specific pAbs against human extracellular signal-regulated kinase 8 were able to perform as a sensitive antibody for cancer case studies.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry using human enterovirus A, B, and C antibodies revealed that only enterovirus B antigen was detected in the liver and adrenal gland in accordance with broad hemorrhagic necrosis (Fig. 2), 9 but not in the placenta. However, enterovirus RNA was extracted using viral RT-PCR not only in the liver (631 copies/cell) and adrenal gland (3510 copies/cell) but also in the placenta (2.2 copies/cell) and spleen (426 copies/cell) (Table 2).…”
Section: Casementioning
confidence: 95%